2020
DOI: 10.3390/su13010046
|View full text |Cite
|
Sign up to set email alerts
|

Schools: An Untapped Opportunity for a Carbon Neutral Future

Abstract: School buildings, like many buildings around the world, are rapidly aging and becoming increasingly inefficient, leading to unnecessary carbon emissions and high utility bills. School buildings can offer some of the most cost-effective carbon abatement opportunities; however, very few schools focus on quantifiable carbon reduction. This is despite the growing emphasis on school sustainability and there is a notable gap in the literature in this area. This study examined 13 schools that participated in an innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Previous studies on LCA of buildings have found results on CC in the range, as this study results. In 2018, a review, published by the Joint Research Centre (JRC) [28], reported a mean value of 23 (ranged between 21.5-26) kg of CO 2 eq./m 2 year in collective buildings and 15 (11)(12)(13)(14)(15)(16)(17)(18) kg of CO 2 eq./m 2 •year in offices buildings, which were the most similar building typology of use to school buildings. Focusing on schools, the key role of the energy-intensive process in schools, such as heating or lighting, have been found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on LCA of buildings have found results on CC in the range, as this study results. In 2018, a review, published by the Joint Research Centre (JRC) [28], reported a mean value of 23 (ranged between 21.5-26) kg of CO 2 eq./m 2 year in collective buildings and 15 (11)(12)(13)(14)(15)(16)(17)(18) kg of CO 2 eq./m 2 •year in offices buildings, which were the most similar building typology of use to school buildings. Focusing on schools, the key role of the energy-intensive process in schools, such as heating or lighting, have been found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of energy, water, and environment systems under the umbrella of multidisciplinary concept of sustainability and circular economy has also explored in some investigations [11][12][13]. The increase in buildings energy efficiency, in both housing and the educational sectors, to reduce energy consumption and CO 2 emissions, including infrastructure and operation and maintenance (O&M) activities, is crucial to decarbonise schools [8,[14][15][16][17][18]. Studies on exploring alternatives have been found, such as district heating systems in Mediterranean climate conditions [19], natural ventilation [20], retrofitting of inefficient buildings using decision support applying parametric analysis [21], and the screening of the best thermal energy storage materials for cooling/ heating and zero carbon buildings [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with the need for environmental conservation which has become the main topic in development activity both globally and in Malaysia, as well as the movement on sustainable development as pledged in Stockholm Conference in 1972, various ministries, departments, and agencies including educational institutions such as schools that have the significant potential to act as a catalyst for community engagement around sustainability [18] are implementing the effort for reducing carbon emissions. As such, the Ministry of Education, Department of Environment, and Institut Alam Sekitar dan Pembangunan (LESTARI), Universiti Kebangsaan Malaysia (UKM) has initiated Sustainable School (Sekolah Lestari -Anugerah Alam Sekitar) to inculcate schools to support the Malaysia Low Carbon Cities movement.…”
Section: Environmental Education For Low-carbon Schoolmentioning
confidence: 99%
“…In this paper we assess the impact of COVID-19 restrictions on school energy usage and quantify the financial savings and environmental impact of these changes. The assessment was done to understand the impact of occupancy on the energy requirements of a school (the delta), and also to quantify base load demand, which could be used to identify untapped potential for savings in aging buildings, similar to a pre-COVID-19 study by (Odell et al, 2021), who showed savings in schools. We focus on five schools in Stellenbosch, in Western Cape province of South Africa and compare their energy usage during the pandemic to the preceding 12 months.…”
Section: An Education-focused Covid-19 Timelinementioning
confidence: 99%